Diseases of the Brain, Head & Neck, Spine c - Hodler, J.; Schulthess, G. K. Von.; Zollikofer, Ch. L.; SpringerLink (Online service) (Milano : Springer Milan, 2008)
This book deals with imaging of diseases of brain, head and neck, and spine. These fields have substantially advanced during the last few years, driven by both clinical developments and advances in imaging technology. The authors contributing to the volume are internationally renowned experts in their field; their chapters are disease-oriented and cover all the relevant imaging modalities, including standard radiography, CT, nuclear medicine with PET, ultrasound and magnetic resonance imaging, as well as imaging-guided interventions. As a result, this book presents a comprehensive review of current knowledge in imaging of the brain, head, neck and spine, as well as in interventional techniques and a selection of "hot topics" in these fields. It will be particularly relevant for residents in radiology, but also very useful for experienced radiologists and clinicians specializing in thoracic disease and wishing to update their knowledge of this rapidly developing field.
Workshops -- Brain Tumors -- Evaluation of the Cerebral Vessels: Endovascular Therapy -- Evaluation of the Cerebral Vessels -- Brain Ischemia -- Hemorrhagic Vascular Pathology - I -- Hemorrhagic Vascular Pathology - II -- Demyelinating Diseases - I -- Demyelinating Diseases - II -- Imaging the Effects of Systemic Metabolic Diseases on the Brain -- Degenerative Brain Disease -- Neuroradiological Diagnosis of Craniocerebral Trauma: Current Concepts -- Nontraumatic Neuroemergencies - I -- Nontraumatic Neuroemergencies - II -- Imaging Approaches to the Epileptic Patient -- Cerebral Infections -- Mass Lesions of the Brain: A Differential Diagnostic Approach -- MRI/MRS of Brain Tumors -- Imaging of Central Nervous System Disease in Pediatrics -- Diseases of the Sella and Parasellar Region -- Orbit and Visual Pathways -- Temporal Bone and Auditory Pathways -- Imaging of Temporal Bone Pathology -- Imaging Diseases of the Pharynx and Oral Cavity -- Imaging of the Larynx and Hypopharynx -- Imaging of the Larynx -- Sinonasal Imaging: Normal Anatomy and Pathologic Processes -- CT and MRI of the Nose, Paranasal Sinuses, and Adjacent Spaces -- Lumbar Degenerative Disc Disease -- Acute Spinal Trauma -- Spinal Cord Inflammatory and Demyelinating Diseases -- Spine Inflammatory and Infectious Diseases -- Nuclear Medicine Satellite Course (3z(BDiamond(3y (B-- Positron Emission Tomography in the Evaluation of Brain Tumors -- Imaging of Dementia -- Clinical SPECT and PET for Management of Patients with Epilepsy -- Magnetic Resonance Essentials for Correlative Imaging of the Brain with PET and SPECT -- Extrapyramidal Syndromes: PET and SPECT -- SPECT/CT of the Spine -- Role of Imaging in Thyroid Disease -- PET/CT Staging and Restaging of ENT Tumors, Pitfalls -- Pediatric Satellite Course (3z(BKangaroo(3y (B-- Pediatric Neuroradiology -- Ultrasonographic Evaluation of the Spinal Sac and Its Content in Neonates and Infants -- Transfontanellar Gray Scale and Doppler Ultrasonography in Newborns -- Diagnostic Imaging of Primary Pediatric Brain Tumors.s
Keywords: Medicine; Radiology; Interventional radiology; Medicine & Public Health; Imaging / Radiology; Diagnostic Radiology; Interventional Radiology; Electronic books